Effect of Packaging Material and Storage Place on Storability of Seeds-A Simulation Study - M.K. GARG; PITAM CHANDRA (Seed Research, 2026)
The adequately tested simulation model was used to compare the storability of pea and onion seeds in different packaging material under the climatic conditions of Leh, Srinagar, Barmer, Poona and Vishakapatnam. The study suggested that Leh and Srinagar were good places for storing onion seed in any type of packaging material. Vishakapatnam was not congenial place for seed storage because of high temperature and high humidity combination. Special protection to seeds from moisture absorption during monsoon was required at Barmer and Poona in order to maintain minimum certification standards. The study indicated that there was an effect of storage place, packaging material, duration of storage and kind of seed on the viability during storage. The model could be effectively used for storing different types of seeds under varying agro-climatic conditions.